2017
DOI: 10.1155/2017/8392435
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phosphorus Slag in Steam-Cured Concrete

Abstract: Steam curing is an effective method to increase the hydration degree of binder containing phosphorus slag. The role of phosphorus slag in steam-cured concrete was investigated by determining the hydration heat, hydration products, nonevaporable water content, pore structure of paste, and the compressive strength and chloride ion permeability of concrete. The results show that elevated steam curing temperature does not lead to new crystalline hydration products of the composite binder containing phosphorus slag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In general, UHPC consists of cement, silica fume, quartz sand, fiber, superplasticizer, and other constituents and exhibits very high compressive strength, high ductility, and outstanding durability [31][32][33][34][35]. High-temperature curing is usually used for UHPC, which is beneficial for the early hydration of cement and mineral admixtures [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In general, UHPC consists of cement, silica fume, quartz sand, fiber, superplasticizer, and other constituents and exhibits very high compressive strength, high ductility, and outstanding durability [31][32][33][34][35]. High-temperature curing is usually used for UHPC, which is beneficial for the early hydration of cement and mineral admixtures [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the gelling property of YPS must be fully activated when increasing the YPS content in concrete. Previous studies have shown that YPS can refine the later pore structure of hardened paste, reduce the chloride ion diffusion coefficient, and improve the compressive strength and concrete durability [ 39 ]. Additionally, the activity of clinker minerals in the dissolution process improved when YPS fluorine (F) and phosphorus (P) were added.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5(b), these samples benefited from the activating effect of the high temperature on the hydration of the composite mineral admixture and the compressive strength of the concrete containing 50% composite mineral admixture is only slightly less than that of the plain cement concrete at 7 d. The compressive strength of the concrete containing 50% composite mineral admixture is slightly greater than of the plain cement concrete at 28 d, and the compressive strength of the concrete containing 50% composite mineral admixture is clearly greater than that of plain cement concrete at 90 d. These results indicate that, for temperature match curing, the concrete containing 50% composite mineral admixture reaches a satisfactory early compressive strength, as well as higher late-age compressive strength, although the compressive strength gain rate of plain cement concrete is low at late ages. This is because concrete cured at a high temperature results in nonuniformly distributed hydration products and a coarser pore structure in hardened paste [24][25][26]. However, the hydration degree of the mineral admixture increases at high temperatures, and the C-S-H gels produced during the hydration of the mineral admixture fill the pore structure of the hardened paste, as a result of which the negative effect of high temperature on development of compressive strength is weakened and the concrete containing mineral admixture cured at high temperature at early ages has a relatively high compressive strength gain rate [26,27].…”
Section: Hydration Heat and Adiabatic Temperature Rise Figures 2(a) mentioning
confidence: 99%
“…This is because concrete cured at a high temperature results in nonuniformly distributed hydration products and a coarser pore structure in hardened paste [24][25][26]. However, the hydration degree of the mineral admixture increases at high temperatures, and the C-S-H gels produced during the hydration of the mineral admixture fill the pore structure of the hardened paste, as a result of which the negative effect of high temperature on development of compressive strength is weakened and the concrete containing mineral admixture cured at high temperature at early ages has a relatively high compressive strength gain rate [26,27]. In addition, the compressive strength of the concrete containing composite mineral admixture B is still greater than for the concrete containing composite mineral admixture A at all ages for temperature match curing.…”
Section: Hydration Heat and Adiabatic Temperature Rise Figures 2(a) mentioning
confidence: 99%
See 1 more Smart Citation